Provision of sufficient transmission capacity for broadband mobilemultimedia a step toward 4G. - Dinis, M. (IEEE Communications magazine)
This article presents a comprehensive description of the mobile broadband communications R&D efforts carried out under the European R&D framework programs-RACE II, ACTS, and IST-but with a special emphasis on the experience gained during the last four years within the SAMBA project. Constraints and requirements specific to this family of systems are identified, and possible technical solutions to mitigate the undesirable effects are outlined. The main features and technology characteristics of the SAMBA project trial platform are described, including the air interface and cell coverage characteristics, for a better understanding of the MBS challenge. The article concludes with a discussion about how MBS integrates with 3G systems add how it paves the way for the next-generation networks